Tingkat Kepuasan Pasien Rawat Jalan Terhadap Pelayanan Kefarmasian di Instalasi Rumah Sakit Sari Asih Ciputat: Level of Satisfaction of Outpatients with Pharmaceutical Services at the Sari Asih Hospital Installation - Tari Dwi Cahyani; Linda Suryanti; Imam Syafi’i; Tyssa Mariyana (Jurnal Ilmiah Farmasi Indonesia (JIFIN), 2024)
Quality health services are those that are able to provide patient satisfaction according to their expectations and needs. Patient satisfaction is an important indicator in assessing the quality of pharmaceutical services because it influences patient loyalty and the hospital’s image. This study aims to determine the level of outpatient satisfaction with pharmaceutical services at the Pharmacy Installation of Sari Asih Hospital Ciputat in 2024. The study employed a descriptive quantitative design using a purposive sampling method. Data were collected through questionnaires distributed to 100 respondents using a non-probability sampling technique with accidental sampling. Patient satisfaction levels were measured based on five dimensions of service quality: tangibles, empathy, reliability, assurance, and responsiveness, analyzed using Likert scales and percentages. The results showed that satisfaction levels for tangibles were 74.24%, empathy 75.24%, reliability 79.92%, assurance 74.52%, and responsiveness 75.92%. Based on these findings, it can be concluded that patients were satisfied with the tangible aspects of service and moderately satisfied with the assurance, reliability, responsiveness, and empathy dimensions of pharmaceutical services at the Outpatient Pharmacy Installation of Sari Asih Hospital Ciputat.